ANALISIS PERILAKU PEMBELIAN IMPULSIF DI E-COMERCE SHOPEE PADA MAHASISWA UNIVERSITAS DI KOTA PEKANBARU - Fachrul Adam; Zulkarnain Zulkarnain; Raden Lestari Garnasih (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
This research aims to analyze the impulsive buying behavior of e-commerce Shoppe among students in Pekanbaru City by looking for the influence of Sales Promotion and Hedonic Shopping Motives on Impulse Buying through Positive Emotion. This research uses primary data, namely data obtained from questionnaires to students who have shopped using Shopee in Pekanbaru City. The secondary data obtained is related to literature related to researchers. The student population of this study was taken from the three largest campuses in Pekanbaru city and sample in this study amounted to 170 people, taken using the Purposive Sampling method. The analytical method used in this research is using Structural Equation Model (SEM) analysis with the help of the SmartPLS program. The research results show that Sales Promotion and Hedonic Shopping Motives influence Positive Emotion. Sales Promotion and Hedonic Shopping Motives influence Impulse Buying. As well as Sales Promotion and Hedonic Shopping Motives influencing Impulse Buying through Positive Emotion. Keyword : Sales Promotion, Hedonic Shopping Motives, Impulse Buying, Positive Emotion